Facultative scavenging on invertebrate cadavers - Foltan, Pavel (Jihočeská univerzita, 2010)
The Ph.D. thesis enclosed focuses on various implications of scavenging by generalist predators on invertebrate cadavers. Comparison of the retention time for invertebrate cadavers in the field, with the detection period for decaying slug material in the guts of the predators is presented and indicates that PCR-based techniques are not able to distinguish between predated and scavenged food items. Disappearance rates for invertebrate cadavers in the field, together with generealist predator preference for dead prey were estimated and their implication on survival strategies of entomopathogenic and molluscicidal nematodes in the cadavers is discussed. Two different strategies were investigated and are presentd in the thesis.
Facultative scavenging on invertebrate cadavers
Keywords: Scavenging; PCR; cadaver; nematodes; Scavenging; PCR; cadaver; nematodes